ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI WAKTU TUNGGU PENGADAAN MATERIAL KONSTRUKSI PADA PROYEK GEDUNG DI KABUPATEN BADUNG - Mudita, Putera Kumarayasa; Sudarsana, I K.; Nadiasa, Mayun (JURNAL SPEKTRAN; Vol 4 No 2 (2016): Vol. 4, No. 2, Juli 2016, 2016)
Abstract : When undertaking construction projects, the smoothflow of materials to the project site must be maintained.Waiting for material, which frequently happens, will have a big impact, especially for large-scale projects that use a lot of labor. If the arrival of the materials is not in accordance with the schedule of material procurement planning, the workers will have nothing to do and the project cost will blow out and there will be delays in project completion time. This research investigates the factors which influence the lead time of construction material procurement in the Badung Regency. Data was obtained by distributing a questionnaire to 50 respondents. A research sample was obtained by purposive sampling aimed at the experts who work on building projects in the Badung regency. Before being used as a research instrument, the questionnaire was tested for the validity of data by using the Pearson Product-Moment correlation and its reliability was tested using the Cronbach alpha method. Processing and data analysis was conducted by Factor Analysis. The research results show there are twenty four variables identified that influence the lead time of construction material procurement on building projects in the Badung regency. All variables can be grouped into seven factors (Factor I, II, III, IV, V, VI, VII). The most dominant factor reviewed based on the percent of variance is Factor I which is formed by six variables being the material production process at the suppliers, the relationships between contractors and suppliers, a lack of material stock at the suppliers, the availability of material transportation, access to the project, and extreme topography.
Keywords: Procurement Lead Time, Construction Material, Factor Analysis